Environmental changes to facilitate weight loss - Kompf, J. (Strength and Conditioning Journal, 2016)
Many eating behaviors are encouraged by environmental triggers, which exist in kitchens, grocery stores, and even in the behavioral norms of social circles. Trainers can encourage an easier course to weight loss by modifying their client's environment.